Parathyroid hormone changes in infants investigated for inflicted injury; an observational retrospective single centre cohort study. (September 2022) - Lewis, L.; Borg, S.; Alison, L.; Hardisty, H.; Parry-Okeden, S.; Kerrin, D.; Chadha, L.; Roberts, K.; Shabani, K.; Offiah, A.C.; Bishop, N.J.
Abstract: Background: Biochemical and haematological testing is recommended in the United Kingdom when inflicted injury is suspected. We examined the associations of test results with radiologically-confirmed fracture(s), and between test results, in a large retrospective observational cohort. Methods: Infants up to age two years presenting with suspected inflicted injury, without clinically or radiologically apparent bone disease, and where a skeletal survey was undertaken during the period 1st August 2013 to 31st December 2020, were included. Biochemical parameters: corrected calcium (cCa); phosphate (P); alkaline phosphatase (ALP); parathyroid hormone (PTH); 25-hydroxyvitamin D (25D); and haematological parameters: haemoglobin (Hb); mean corpuscular haemoglobin (MCH); mean corpuscular haemoglobin content (MCHC); mean corpuscular volume (MCV); platelet count were collated together with the results of the radiological assessments. Findings: Of 332 eligible infants (190 male), 142 (84 male) had fracture(s) and/or intracranial injury. Mean PTH in the non-fracture group (n measured 50/190) was 27.3 ng/l; in those with intracranial injury alone (n measured 9/23) was 39.4 ng/l; in those with fracture alone (n measured 62/84) was 45.0 ng/l; and in those with fracture and intracranial injury (n measured 20/35) 51.8 ng/l. F-test of multiple means = 0.0369. There was no difference in 25D between the groups. Interpretation: PTH was raised in infants who had fracture(s), intracranial injury or both. A single raised PTH may not necessarily be an indicator of prior disturbed skeletal health in these circumstances. The relevance of vitamin D status and interpretation of data from biochemical testing should be informed by the overall presentation in suspected inflicted injury cases. A single raised PTH may be a consequence of the child's injuries rather than prior disturbed bone health.